SORGENTINA-RF FUSION NEUTRON PLANT: PRELIMINARY DESIGN OF THE BIOSHIELDING IN COMPLIANCE WITH DOSE CONSTRAINTS FOR WORKERS EXPOSURE. Issue 18 (8th September 2022) - Ferrari, P; Contessa, G M; Moro, F; Gadani, G; Lepore, L; Pietropaolo, A; ,
Abstract: An accelerator-driven 14 MeV neutron source of new concept, denominated SORGENTINA-RF, will be installed in ENEA Brasimone Research Centre, to test the feasibility of producing radionuclides of medical relevance using fusion neutrons. The main goal of the facility is generating 99 Mo as precursor of 99m Tc, a radionuclide widely used in nuclear medicine diagnostic procedures, using the 14 MeV fusion neutrons produced by the plant. This work describes the study performed for the design of a proper shielding structure that aims at fulfilling the requirement of 0.01 mSv/h dose rate limit on the external surface of the shielding during beam-on operations. The proposed shielding consists of a layered structure composed of 2 m standard concrete and 1 m baritic concrete. The design is still in the preliminary phase to assess the feasibility and the economic issues as well as structural impact of the shielding structure.